Infrageneric classification of Geranium (Geraniaceae) based on fruit and seed morphology - Keshavarzi, Maryam (Acta Biologica Szegediensis, 2015)
Geranium comprises 23 to 25 annual and perennial species in Iran. Fruit and seed morphology of 9 taxa are examined to investigate utility of infrageneric system of Geranium in Iran. Totally 19 characters of fruits and seeds were evaluated by stereomicroscopy and scanning electron microscopy. Fruit and seed morphological markers are of evolutionary and taxonomic importance in Geranium species. Species relationships and infrageneric classification have been evaluated by multivariate statistical analysis. Diagnostic features are presence of glandular hairs in mericarp and hair length, seed width and mericarp texture. Taxa of two subgenera are clearly separated based on selected fruit and seed characters.